Protein profiles of three species of malaysian sea cucumber; holothuria edulis lesson, H. scabra jaeger and stichopus horrens selenka - Hashim, Ridzwan; Z., Farah Hanis; Mohd Daud, Jamaluddin; Althunibat, Osama Yousef (EuroJournals Publishing, Inc., 2012)
Three local species of sea cucumbers; Holothuria edulis Lesson, H. scabra Jaeger and Stichopus horrens Selenka were studied for their body walls protein profiles using sodium dodecyl sulphate polyacylamide gel electrophoresis (SDS-PAGE). Their body walls were subjected to extraction process using lysis and resuspension buffers. The protein concentration was based on bovine serum albumin as standard. Analysis of the protein extract of the three species of sea cucumber revealed at least 11 type of proteins with molecular weight ranging from 20 kDa – 125 kDa. As for the protein profiles, significant difference in the protein binding patterns were noticed. The results showed the molecular weight of protein varied among species; 20 – 54 kDa for H. edulis and 54 – 125 kDa for H. scabra. However, protein fraction for S. horrens failed to be detected using this technique.